Associations of occupational stress, workplace violence, and organizational support on chronic fatigue syndrome among nurses. (24th February 2020) - Li, Mengyao; Shu, Qianyi; Huang, Hao; Bo, Wen; Wang, Lulu; Wu, Hui
Abstract: Aims: Chronic fatigue syndrome is an agnogenic disease worldwide. Nurses are at a high risk of chronic fatigue syndrome. However, no research has been done to examine the associations of workplace violence, organizational support, and occupational stress with chronic fatigue syndrome among Chinese nurses. This study aimed to examine effects of these factors on chronic fatigue syndrome in this occupational group. Design: Cross‐sectional. All participants voluntarily completed a questionnaire survey. Methods: The study was conducted in Liaoning province from December 2017–January 2018. Self‐administered questionnaires were distributed to 1, 200 nurses, including Effort‐Reward‐Imbalance, Workplace Violence Scale, Survey of Perceived Organizational Support, together with age, gender, marital status, education levels, physical activities, job rank, monthly income, and weekly working hours. Complete responses were obtained from 1, 080 (90%) participants. Chronic fatigue syndrome was diagnosed by doctors according to the Centers for Disease Control and Prevention criteria. Multivariable logistic regression was performed to examine these independent risk factors. Results: The prevalence of chronic fatigue syndrome was 6.76%. The results of logistic regression analysis showed that nurses who experienced serious higher levels of overcommitment, workplace violence and less organizational support were more likely to be classified as chronic fatigue syndrome. Conclusion: There was a high prevalence of chronic fatigue syndrome. Lower workplace violence, more organizational support and lower overcommitment could be effective resources for reducing chronic fatigue syndrome. Impact: Workplace violence, organizational support, and occupational stress were related to chronic fatigue syndrome, which helped to explain why Chinese nurses suffered higher prevalence of chronic fatigue syndrome. Overcommitment explained chronic fatigue syndrome better than Effort/Reward Ratio, so intrinsic stress played a more critical role than extrinsic stress in chronic fatigue syndrome. Chinese nurses suffered serious sleep disorders and impairment of concentration and memory. These symptoms might also attribute to serious occupational stress, unsafe and unsupportive working environment. Creating a safe and supportive working environment, relieving intrinsic occupational stress should be considered as an institutional strategy to early prevent chronic fatigue syndrome. Abstract : 目的: 慢性疲劳综合征是一种病因不明的世界性疾病。护士患慢性疲劳综合征的风险很高。然而, 目前尚无针对中国护士工作场所暴力、组织支持和职业压力与慢性疲劳综合征之间的关系的研究。本研究旨在探讨这些因素对该职业人群慢性疲劳综合征的影响。 设计: 横断面。所有参与者自愿完成问卷调查。 方法: 本研究于2017年12月至2018年1月在辽宁省进行。共向1, 200 名护士发放自填问卷, 包括付出收获不平衡、工作场所暴力量表、组织支持感问卷, 以及年龄、性别、婚姻状况、教育程度、体育锻炼、职级、月收入、每周工作时间调查。共有1, 080名(90%)参与者给出了完整答复。慢性疲劳综合征由医生根据疾病预防控制中心标准进行诊断。同时采用多变量逻辑回归对此类独立风险因素进行分析。 结果: 慢性疲劳综合征患病率为6.76%。逻辑回归分析结果表明, 护士如果经历重大的、较高水平的过度承诺, 工作场所暴力和较少的组织支持, 更容易患有慢性疲劳综合征。 结论: 慢性疲劳综合征患病率较高。减少工作场所暴力、提供更多的组织支持以及减少过度承诺可有助于降低慢性疲劳综合症的患病概率。 影响: 工作场所暴力、组织支持、职业压力与慢性疲劳综合征相关, 这有助于解释中国护士慢性疲劳综合征患病率较高的原因。相对于付出/获得比, 过度承诺更适合用于解释慢性疲劳综合征的患病原因, 因此内在压力比外在压力对慢性疲劳综合征中的影响更为严重。中国护士普遍存在严重的睡眠障碍, 注意力和记忆力减退情况。这些症状也可归因于较高的职业压力以及工作环境缺乏安全性和支持性。创造安全且具支持性的工作环境、缓解内在的职业压力应被视为一种早期预防慢性疲劳综合征的制度策略。